Green synthesis of metal nanoparticles using microorganisms and their application in the agrifood sector - Bahrulolum, Howra; Nooraei, Saghi; Javanshir, Nahid; Tarrahimofrad, Hossein; Mirbagheri, Vasighe Sadat; Easton, Andrew J.; Ahmadian, Gholamreza (Journal of nanobiotechnology, 2021)
The agricultural sector is currently facing many global challenges, such as climate change, and environmental problems such as the release of pesticides and fertilizers, which will be exacerbated in the face of population growth and food shortages. Therefore, the need to change traditional farming methods and replace them with new technologies is essential, and the application of nanotechnology, especially green technology offers considerable promise in alleviating these problems. Nanotechnology has led to changes and advances in many technologies and has the potential to transform various fields of the agricultural sector, including biosensors, pesticides, fertilizers, food packaging and other areas of the agricultural industry. Due to their unique properties, nanomaterials are considered as suitable carriers for stabilizing fertilizers and pesticides, as well as facilitating controlled nutrient transfer and increasing crop protection. The production of nanoparticles by physical and chemical methods requires the use of hazardous materials, advanced equipment, and has a negative impact on the environment. Thus, over the last decade, research activities in the context of nanotechnology have shifted towards environmentally friendly and economically viable ‘green’ synthesis to support the increasing use of nanoparticles in various industries. Green synthesis, as part of bio-inspired protocols, provides reliable and sustainable methods for the biosynthesis of nanoparticles by a wide range of microorganisms rather than current synthetic processes. Therefore, this field is developing rapidly and new methods in this field are constantly being invented to improve the properties of nanoparticles. In this review, we consider the latest advances and innovations in the production of metal nanoparticles using green synthesis by different groups of microorganisms and the application of these nanoparticles in various agricultural sectors to achieve food security, improve crop production and reduce the use of pesticides. In addition, the mechanism of synthesis of metal nanoparticles by different microorganisms and their advantages and disadvantages compared to other common methods are presented.